Walking the green line: Government sponsored R&D and clean technologies - Francesco Rentocchini; Antonio Vezzani; Sandro Montresor (European Commission, Joint Research Centre (JRC), 2024)
We examine whether government sponsored R&D induces the development of clean technologies with a high impact on subsequent technological development. The analysis uses information on USPTO patents granted between 2005 and 2015 and combines different methods to control for possible sorting of projects into public funding and for non-random (public) treatment. We also assess the distributional effect of government sponsored R&D. Results show that patents from public funded projects have a significantly higher impact and that this is particularly true for highly cited patents, thus supporting a role for technology-push policies in determining a clean technological transition.
Keywords: 330